How inclusive is volcanology? Insights from global bibliometric analyses - Lerner, Geoffrey A. (2023)
In this study, we use bibliometric methods to assess the way in which local researchers are included in volcanological publications by comparing the affiliation of authors with the country in which researched volcanoes are located. Globally, 40 % of articles about a specific volcano do not include an author whose affiliation is based in the country where the volcano is located (a locally domiciled author), while 56 % are led by authors not based in the country of the volcano. Over the past three decades, first-authorship rates among local researchers have not increased. However, local researchers have becomemore frequently included as co-authors in research led by researchers domiciled elsewhere. We provide examples of how this bibliometric analysis can be used to evaluate several specific inclusion-related topics. The results of these analyses suggest that there is room for improvement in inclusivity in volcanological research and cause for reflection on how we collaborate with international partners.